2016
DOI: 10.1063/1.4962323
|View full text |Cite
|
Sign up to set email alerts
|

Transition and post-transition metal ions in borate glasses: Borate ligand speciation, cluster formation, and their effect on glass transition and mechanical properties

Abstract: A series of transition and post-transition metal ion (Mn, Cu, Zn, Pb, Bi) binary borate glasses was studied with special consideration of the cations impact on the borate structure, the cations cross-linking capacity, and more generally, structure-property correlations. Infrared (IR) and Raman spectroscopies were used for the structural characterization. These complementary techniques are sensitive to the short-range order as in the differentiation of tetrahedral and trigonal borate units or regarding the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 79 publications
10
82
1
Order By: Relevance
“…An echometer (model 1077, Karl Deutsch GmbH) working with an accuracy of ±1 ns was employed. More information on ultrasonic measurements and how elastic properties such as shear modulus G, bulk modulus K, and Young's modulus E, and Poisson ratio ν can be found elsewhere (Limbach et al 2015;Möncke et al, 2016).…”
Section: General Glass Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…An echometer (model 1077, Karl Deutsch GmbH) working with an accuracy of ±1 ns was employed. More information on ultrasonic measurements and how elastic properties such as shear modulus G, bulk modulus K, and Young's modulus E, and Poisson ratio ν can be found elsewhere (Limbach et al 2015;Möncke et al, 2016).…”
Section: General Glass Characterizationmentioning
confidence: 99%
“…In general, both processes, densification and shear flow are sensitive toward changes in strain rate (Shikimaka et al, 2016); the contribution of each, however, depends on composition, atomic packing density, and network connectivity (Yoshida et al, 2005;Limbach et al, 2014;Möncke et al, 2016). Shikimaka et al (2016) concluded densification to be triggered by shear and pressure.…”
Section: The Effect Of Strain Rate On the Deformation Mechanismmentioning
confidence: 99%
“…Lead borate glasses have shown to exhibit a large glass forming region . Because of the large difference between the masses of lead and boron atoms are vibrational modes of PbO polyhedral and the borate network well separated in the IR and Raman spectra . Lead borate glasses have been used successfully as efficient laser host material .…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the un‐doped ZnB glass mainly consists of boroxol and borate rings. ZnO cause a partial disproportionation of the (BØ 2 O) − and (BØ 4 ) − groups to (BØO 2 ) 2− and BØ 3 groups . However, Zn 2+ with high field strength is not only a modifier ion.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of most un‐doped borate and borosilicate glasses used for these investigations is relatively well understood and was studied before with different methods. Many papers were published by us and other authors . But unfortunately, it was not possible for us up to now, to determine the local structure of Tb 3+ , or other RE 3+ ions, in the selected borate and borosilicate glasses in more detail.…”
Section: Discussionmentioning
confidence: 99%